Our futures in mind uploading: public perceptions and narratives - Thornton, Angela Claire (2024)
Advances in neurotechnology, have immense potential but also pose significant ethical challenges since they implicate fundamental human capacities such as identity, agency, and autonomy. Hence the development of neurotechnology is being prioritised by intergovernmental organisations such as the United Nations Educational, Scientific and Cultural Organization (UNESCO) and The Organisation for Economic Cooperation and Development (OECD). The aim is to ensure neurotechnology development is grounded in principles of Responsible Research and Innovation (RRI) and is responsive to all stakeholders.